The Effect of Acupressure at Lr 3 And Sp 6 Point on The Pain Scale Among Post Sectio Caesarea Patient at Regional Public Hospital of Banyumas - Tuswati Tuswati; Iwan Purnawan; Mekar Dwi Anggraeni (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2019)
Background. Pain is the major complaint felt by mothers with post sectio caesarea that they are afraid making any mobilization. Early mobilization of post sectio caesarea are highly necessary to accelerate the wound healing. Acupressure is one of non-pharmacological therapies to reduce pain. Acupressure has the ability to release endorphins. Accupressure at LR 3 and SP 6 point stimulate the endorphin expulsion. Objective. This research aimed to examine the effect of acupressure at LR 3 and SP 6 point on the pain scale of the post sectio caesarea patient at Regional Public Hospital of Banyumas.Method. The research was a quasi-experimental and pretest-posttest design with control group. Sample were collected using a consecutive sampling technique. The samples were 40 patients consisting of 20 patients classified into the intervention group and 20 patients classified into the control group. The pain was measured using a numeric rating scale. The intervention group was administered with acupressure performed at LR3 and SP 6 point for 30 times on each point while the control group was administered with internal respiration for 10 minutes. The data were analyzed using Wilcoxon and Mann Whitney test with the significance level of ? ? 0.05.Result. The results of Wilcoxon test showed that accupressure at LR 3 and SP 6 point influenced the pain scale of those classified into the intervention group with the value of p = 0.000 (? < 0.05) but does not influence those classified into the control group with the value of p = 0.157 (? > 0.05). Meanwhile, the result of Mann Whitney test showed that there was an significant difference between the intervention and control group post test score with the value of p = 0.000 (? < 0.05).Conclusion. acupressure at LR 3 and SP 6 point significantly effect the pain scale of post sectio caesarea patient.